2020
DOI: 10.1021/acs.jpcc.9b07114
|View full text |Cite
|
Sign up to set email alerts
|

On the Overlooked Critical Role of the pH Value on the Kinetics of the 4-Nitrophenol NaBH4-Reduction Catalyzed by Noble-Metal Nanoparticles (Pt, Pd, and Au)

Abstract: The reduction of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP) with sodium borohydride (NaBH4) in aqueous media is by far the most widely used reaction for testing the catalytic performance of a large variety of metal nanoparticles (MNPs) using UV/vis absorption spectroscopy. Huge differences in the kinetic rate constant of the catalytic 4-NP to 4-AP conversion as a function of material composition, size, and morphology have been reported by many different groups; so far, these have been exclusively attributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(75 citation statements)
references
References 32 publications
5
69
1
Order By: Relevance
“…In the case of 150 eq, the pH was 9.69, and in the case of 200 eq, the pH was 9.93. This slight change influenced the NaBH 4 hydrolysis, which was faster, leading to higher formation of reactive Pd-H at the surface of NPs as described by Grzeschik and coworkers [33]. They found that the pH value has an influence on the kinetics of 4-Nip reduction and that by decreasing the initial pH value, the reaction becomes much faster.…”
Section: Influence Of Temperature (Derivation Of Thermodynamic Paramementioning
confidence: 70%
“…In the case of 150 eq, the pH was 9.69, and in the case of 200 eq, the pH was 9.93. This slight change influenced the NaBH 4 hydrolysis, which was faster, leading to higher formation of reactive Pd-H at the surface of NPs as described by Grzeschik and coworkers [33]. They found that the pH value has an influence on the kinetics of 4-Nip reduction and that by decreasing the initial pH value, the reaction becomes much faster.…”
Section: Influence Of Temperature (Derivation Of Thermodynamic Paramementioning
confidence: 70%
“…To investigate the catalytic activity of the deposited nanocrystals, polymer samples treated with different AgNO 3 concentrations, exhibiting the broadest range of deposited silver, were studied (see Figure 3 b). The efficiency of the silver catalyst was tested by reduction of 4-NP to 4-AP, which is an extensively investigated process commonly used for catalyst activity tests [ 17 , 18 , 19 , 56 , 57 , 58 , 59 , 60 ]. The reaction was monitored by in-line measurement of absorbance at the column outlet ( Figure 6 a).…”
Section: Resultsmentioning
confidence: 99%
“…As the NaBH 4 concentration was in high excess [ 61 ], a solution with high pH was used [ 56 ], and oxygen was removed [ 59 , 60 ]; therefore, Equation (1) can be further simplified into pseudo-first-order reaction kinetics with an apparent rate constant [ 56 ]: for a continuous tubular reactor ( Figure 6 ), resulting in the following expression: where k’ is the apparent rate pseudo-first-order rate constant [min −1 ], k cat ’ is the apparent rate pseudo-first-order catalytic rate constant [min −1 g −1 ], A in / A out and C in / C out are the absorbance and concentration ratios of 4-NP at the inlet and outlet of the column with subtracted baseline (solution without 4-NP), F is the flow rate, V c is the column volume, ε is the column porosity, and t r is the residence time.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction can be monitored online via UV-Vis since in the reaction mixture the 4-NP is rapidly converted into 4-nitrophenolate (reaction pH is 9) that has a characteristic absorption at 400 nm and the product 4-aminophenol (4-AP) has an absorption at 300 nm [ 17 , 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%